Liquid‐State Templates for Constructing B, N, Co‐Doping Porous Carbons with a Boosting of Potassium‐Ion Storage Performance. Issue 4 (18th December 2020) - Feng, Wenting; Feng, Nianyun; Liu, Wei; Cui, Yongpeng; Chen, Chen; Dong, Tiantian; Liu, Shuang; Deng, Weiqiao; Wang, Huanlei; Jin, Yongcheng
Abstract: Template‐assistant design and fabrication of porous carbon electrode materials has experienced great progress throughout the past decades and yielded lots of successes via various gas or solid state templates. Nevertheless, liquid‐state templates are rather rare in preparing porous carbon materials to date. In this work, melting B2 O3 beads are used as both templates and a B dopant, leading to unique B, N co‐doping hierarchically porous carbons containing a "bubble pool"‐like skeleton built of interconnected carbon nanobubbles. Notably, an interesting amending effect of doped B atoms on the N‐doped carbon network can be identified for the first time, which creates a "paddy field"‐like hybrid microstructure with the co‐existence of sp 2 short‐range order and sp 3 defective areas, leading to an ideal model of carbon materials with both good conductivity and high capacity. Together with the rich ion diffusing pathways and the structural integrity of the "bubble pool"‐like skeleton, the resultant electrode delivers a comprehensive K‐ion storage performance. Therefore, the findings demonstrate the unique pore‐making merits of liquid state templates, which may open the door for exploring porous carbons with more innovations of microstructures and functionalities for applications in energy storage and other fields. Abstract : B, N co‐doping porous carbons with "bubble pool"‐like microstructure are readily fabricated via a liquid‐state template strategy. Benefiting from an interesting mending effect of B atoms for N doped carbon networks, the obtained nanobubbles exhibit the co‐existence of good conductivity and high capacity, leading to a comprehensive K‐ions storage ability.